2019
DOI: 10.32604/cmes.2019.08275
|View full text |Cite
|
Sign up to set email alerts
|

Some Remarks on the Method of Fundamental Solutions for Two-Dimensional Elasticity

Abstract: In this paper, some remarks for more efficient analysis of two-dimensional elastostatic problems using the method of fundamental solutions are made. First, the effects of the distance between pseudo and main boundaries on the solution are investigated and by a numerical study a lower bound for the distance of each source point to the main boundary is suggested. In some cases, the resulting system of equations becomes ill-conditioned for which, the truncated singular value decomposition with a criterion based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…This same result is found as number of source points increases (Golberg & Chen, 1998, Liu, 2012. Some strategies to circumvent ill-conditioning were considered in Chen et al (2006), Young et al (2008), Chen et al (2016) and Hematiyan et al (2016).…”
Section: /15supporting
confidence: 61%
“…This same result is found as number of source points increases (Golberg & Chen, 1998, Liu, 2012. Some strategies to circumvent ill-conditioning were considered in Chen et al (2006), Young et al (2008), Chen et al (2016) and Hematiyan et al (2016).…”
Section: /15supporting
confidence: 61%
“…The exact solution for radial displacement and stresses are uniform over the boundary of the disk; however, the solutions obtained by the MFS have some oscillations over the boundary in the cases with smaller values of K. It is observed that by increasing the value of K, the accuracy of the solutions is enhanced. The MFS results for isotropic elastostatic problems [40] show that K = 0.85 yields sufficiently accurate results; however, as it is seen in Fig. 5, the MFS results with K = 0.9 for the present example, which has a moderate degree of anisotropy, are not sufficiently accurate.…”
Section: A Circular Domainmentioning
confidence: 53%
“…Therefore, a parameter which describes the distance between main and pseudo boundaries relative to the number of soure points should be considered in the next numerical studies. Hematiyan et al [34,40] defined the source point location parameter for this purpose. The source point location parameter can be defined using Fig.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in [4,5] was introduced the approach that dispenses with the use of the RBF method and we are going to derive it for the time dependent boundary value problem for the hyperbolic elasticity equation. There are a few studies for the elastodynamic problems that are based on the MFS-RBF, see [14,15,17] or on the boundary integral equations method [8,10]. This is due to the important application of the problem, for example, in ISSN 20785097.…”
Section: Introductionmentioning
confidence: 99%